Chromosome-level genome assembly and anticoagulant protein annotation of the buffalo leech Hirudinaria bpling (Hirudinea: Hirudinidae) - Muhammad Salabat Khan; Christian Müller; Baozhen Zhou (BMC Genomics)
Abstract This study aimed to obtain and analyze the chromosome-level genome assembly of Hirudinaria bpling, a species vital for aquatic ecosystem health and medical research. Understanding its genomic information is crucial for advancing its medical applications and elucidating its ecological role. We assembled the genome of H. bpling using a combination of PacBio HiFi long reads, Illumina sequencing, and Hi-C chromosome conformation capture techniques. This approach allowed us to achieve a high-resolution genome assembly with detailed chromosomal organization. The final genome assembly of H. bpling is 144.08 Mb, with an N50 size of 11.27 Mb, anchored onto thirteen pseudo-chromosomes. BUSCO analysis indicated a genome completeness of 96.20%. We annotated a total of 20,126 protein-coding genes and identified 18.80% repetitive elements within the genome. Phylogenetic analysis included nine other leech species, positioning H. bpling as a sister taxon to Hirudo manillensis. A comparative analysis focused on the identification of putative anticoagulant proteins (e.g. Hirudin, Antistasin, Hirustasin, Therostasin, Bdellastasin, Guamerin/Piguamerin, Gelin, Bplins, Saratin, Eglin C, Bdellin B-3, LDTI, Hyaluronidase, Destabilase, Apyrase, Leech carboxypeptidase inhibitor, Gamma-glutamyl transpeptidase, Lefaxin, Progranulin), identifying conserved regions and evolutionary relationships among these proteins across different leech species. As a medically significant species, H. bpling offers promising opportunities for research into anticoagulant therapies. This study provides a comprehensive genomic and phylogenetic analysis of H. bpling, offering new insights into leech genomics and the evolution of anticoagulant genes. The findings enhance our understanding of the genetic and evolutionary mechanisms underlying anticoagulant production in leeches.